Character education in Serat Sabdajati the last R.Ng. Ranggawarsita’s work - Purwadi Purwadi; Venny Indria Ekowati; Avi Meilawati; Doni Dwi Hartanto; Sri Hertanti Wulan; Galang Prastowo; Ghis Nggar Dwiadmojo; Nurhidayati Nurhidayati (Jurnal Cakrawala Pendidikan, 2022)
The present study aimed to explore character education and philosophical values in the Ranggawarsita’s work entitled Serat Sabdajati. A qualitative method was applied in this study using hermeneutic design. The National Library of the Republic of Indonesia Collection of Serat Sabdajati was used as the primary data source in this study. The data collected in this study were the lingual units including the words, phrases, clauses and sentences in the verses of the Serat Sabdajati. The collected data were analyzed qualitatively using hermeneutic approach. The results reported several character and philosophical values found in the serat (manuscript), which include: 1) spiritual values including laku prihatin (caring), nglaras ati (harmonize the heart) , ngesthi rahayu (looking for salvation), jatining kawruh (true knowledge), ambuka wiwaraning dhiri (open up), manunggaling kawula Gusti (unity with the God), kemating pating pratitis (viewing the death distinctly); 2) religious values including andel mring Hyang (believe in God), temen tinemu (those who sow will reap); 3) social values including sasmita yekti (understand the truth), memayu hayuning sasama (maintain community safety). This study concluded that human needs to always aware of their origin and the place to return to. A comprehensive discussion was presented by comparing the results of the present study and the previous studies.